The Effect of Time Management on Student’s Interest in Learning Mathematics - Rambe, Halimatu Sadyah; Siregar, Sakinah Ubudiyah (Jurnal Basicedu, 2022)
This study aims to determine the effect of time management on student interest in learning at Mts s Addinussyarifiah in class VII using time management indicators. Time management is the process of consciously planning and controlling the time spent on certain activities, especially to increase effectiveness, efficiency, and productivity. From the results of the study, the conclusions obtained are: 1. Time management for class VIII Mts s Addinussyarifiah 2021 belongs to the sufficient category from the indicators that have been implemented, 2. From the value of the mathematics learning outcomes of class VIII Mts s Addinussyarifiah 2021 students are classified as good category according to the distribution of the questionnaire, 3. There is an influence between time management and interest in learning mathematics in class VIII Mts s Addinussyarifiah which is quite significant based on descriptive analysis of the indicators that have been implemented.